The war on drugs in sport: a perspective from the front-line - Mendoza, J. (Clinical Journal of Sport Medicine, 2002)
CONTEXT: Recent international developments have served to solidify the international approach to doping in sport. The development of the World Anti-Doping Agency (WADA) has resulted in new, coordinated efforts to address this important sport issue. An array of new efforts and initiatives has been initiated by the new agency. The Sydney and Salt Lake City Olympics were characterized by intensive efforts to minimize doping. The antidoping environment is evolving rapidly, and several profoundly important developments will take place in the immediate future. OBJECTIVES: To outline the challenges, opportunities, and changing circumstances of the current antidoping environment so that sport medicine practitioners might understand the context in which a variety of new initiatives and approaches will develop. At the same time, to ensure that practitioners understand the importance of appropriately developed and delivered antidoping policies, programs, and procedures, and the need for their harmonization. To ensure that sport medicine practitioners appreciate the need for a comprehensive approach to doping control, i.e., programs that include much more than drug testing. DATA SOURCE: A review of relevant policy documents derived from a variety of sport and antidoping organizations; selected references drawn from MEDLINE; and materials prepared by colleagues drawn from the international antidoping community. CONCLUSIONS: The increased global effort to address doping is welcome. It will require that several critical issues be addressed that will test the resolve of all involved.